Multidisciplinary clinic approach improves overall survival outcomes of patients with metastatic germ-cell tumors. (10th November 2017) - Albany, C; Adra, N; Snavely, A C; Cary, C; Masterson, T A; Foster, R S; Kesler, K; Ulbright, T M; Cheng, L; Chovanec, M; Taza, F; Ku, K; et al.
Abstract: Background: To report our experience utilizing a multidisciplinary clinic (MDC) at Indiana University (IU) since the publication of the International Germ Cell Cancer Collaborative Group (IGCCCG), and to compare our overall survival (OS) to that of the National Cancer Institute (NCI) Surveillance, Epidemiology, and End Results (SEER) Program. Patients and methods: We conducted a retrospective analysis of all patients with metastatic germ-cell tumor (GCT) seen at IU from 1998 to 2014. A total of 1611 consecutive patients were identified, of whom 704 patients received an initial evaluation by our MDC (including medical oncology, pathology, urology and thoracic surgery) and started first-line chemotherapy at IU. These 704 patients were eligible for analysis. All patients in this cohort were treated with cisplatin–etoposide-based combination chemotherapy. We compared the progression-free survival (PFS) and OS of patients treated at IU with that of the published IGCCCG cohort. OS of the IU testis cancer primary cohort ( n = 622) was further compared with the SEER data of 1283 patients labeled with 'distant' disease. The Kaplan–Meier method was used to estimate PFS and OS. Results: With a median follow-up of 4.4 years, patients with good, intermediate, and poor risk disease by IGCCCG criteria treated at IU had 5-year PFS of 90%, 84%, and 54% and 5-year OS of 97%, 92%, and 73%, respectively. The 5-year PFS for all patients in the IU cohort was 79% [95% confidence interval (CI) 76% to 82%]. The 5-year OS for the IU cohort was 90% (95% CI 87% to 92%). IU testis cohort had 5-year OS 94% (95% CI 91% to 96%) versus 75% (95% CI 73% to 78%) for the SEER 'distant' cohort between 2000 and 2014, P -value <0.0001. Conclusion: The MDC approach to GCT at high-volume cancer center associated with improved OS outcomes in this contemporary dataset. OS is significantly higher in the IU cohort compared with the IGCCCG and SEER 'distant' cohort.